Hard surface pens for finishing cattle - Perry, H.B.; Larson, G.H.; Lipper, R.I.; Smith, E.F.; Boren, Fred W. (Kansas Agricultural Experiment Station, 2011)
Each of two lots was 24’ x 92’, one completely surfaced with concrete; the other, soil except for a 24’ x 16’ concrete feeding floor where the cattle stood to eat from a fence line feeder.
Keywords: Beef; Finishing cattle; Concrete pens; Gain